A phase‐1 pharmacokinetic optimal dosing study of intraventricular topotecan for children with neoplastic meningitis: A pediatric brain tumor consortium study1. Issue 4 (21st September 2012) - Blaney, Susan M.; Tagen, Michael; Onar‐Thomas, Arzu; Berg, Stacey L.; Gururangan, Sri; Scorsone, Kathleen; Su, Jack; Goldman, Stewart; Kieran, Mark W.; Kun, Larry; Boyett, Jim; Stewart, Clinton
Abstract Purpose We performed a phase‐1 pharmacokinetic optimal dosing study of intraventricular topotecan (IT), administered daily 5×, to determine whether, the maximum tolerated dose of IT topotecan was also the pharmacokinetic optimal dose. Patients and Methods Patients received topotecan administered through an intraventricular access device (0.1 or 0.2 mg/dose), daily × 5 every other week 2× (Induction); every 3 weeks × 2 (Consolidation); then every 4 weeks for up to 11 courses (Maintenance). Ventricular CSF pharmacokinetic studies were performed on day 1, week 1 of induction, and in a subset of patients after a single intralumbar topotecan dose on day 1, week 3. Results Nineteen patients were enrolled. All were evaluable for toxicity and 18 were assessable for pharmacokinetics. Arachnoiditis requiring corticosteroid therapy occurred in or one of three patients at the 0.1 mg dose level and two of the initial three patients enrolled at the 0.2 mg dose level. All subsequent patients were therefore treated with concomitant dexamethasone. Pharmacokinetic evaluation after accrual of the first seven patients revealed that a topotecan lactone concentration >1 ng/ml for 8 hours was attained in all patients and thus, further dose escalation was not pursued. Results of simulation studies showed that at the dose levels evaluated, >99.9% of patients are expected to achieve CSF topotecan lactone concentrations >1 ng/ml for at least 8 hours. Conclusion Intraventricular topotecan, 0.2 mg, administered daily for 5 days with concomitant dexamethasone is well tolerated and was defined to be the pharmacokinetic optimal dose in this trial. Pediatr Blood Cancer 2013; 60: 627–632. © 2012 Wiley Periodicals, Inc.